Liver resection for hepatocellular carcinoma in patients without cirrhosis. Issue 1 (6th November 2012) - Thelen, A.; Benckert, C.; Tautenhahn, H.‐M.; Hau, H.‐M.; Bartels, M.; Linnemann, J.; Bertolini, J.; Moche, M.; Wittekind, C.; Jonas, S.
Abstract Background: Data on liver resection for hepatocellular carcinoma (HCC) without cirrhosis are sparse. The present study was conducted to evaluate the indications and results of liver resection for HCC with regard to safety and efficacy. Methods: Data for patients who had liver resection for HCC without cirrhosis between January 1996 and March 2011 were retrieved retrospectively using a prospective database containing information on all patients who underwent hepatectomy for HCC. Patient and tumour characteristics were analysed for influence on overall and disease‐free survival to identify prognostic factors by univariable and multivariable analysis. Results: The 1‐, 3‐ and 5‐year overall survival rates after resection with curative intent for HCC without cirrhosis were 84, 66 and 50 per cent respectively. Disease‐free survival rates were 69, 53 and 42 per cent respectively. The 90‐day mortality rate was 4·5 per cent (5 of 110 patients). Surgical radicality and growth pattern of the tumour were independent prognostic factors for overall survival. Disease‐free survival after resection with curative intent was independently affected by growth pattern and by the number and size of tumour nodules. Conclusion: Liver resection for HCC without cirrhosis carries a low perioperative risk and excellent long‐term outcome if radical resection is achieved. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.